A new species of Vehilius Godman, 1900 (Lepidoptera, Hesperiidae, Hesperiinae) endemic to the Caatinga, northeastern Brazil: taxonomy, biology and behavior - Souza, Janiely Alves De; Medeiros, Adalberto Dantas De; Dolibaina, Diego Rodrigo; Kerpel, Solange Maria (Zootaxa, 2023)
A new species belonging to the genus Vehilius Godman, 1900, Vehilius jabre Medeiros, Souza & Kerpel sp. nov., endemic to the Caatinga biome, northeastern Brazil, is here described based on data from adult and immature stages. Information about the biology, hostplant, distribution, and adult and larval behavior of the new species is provided. The new species is morphologically similar to Vehilius warreni (Weeks, 1901), but can be distinguished by a set of characters on wings and male and female genitalia. Adults and genitalia for both sexes of V. jabre sp. nov. and V. warreni are illustrated and compared.